The Biosynthesis of Lipooligosaccharide from Bacteroides thetaiotaomicron - Jacobson, Amy N. (mBio, 2018)
Lipopolysaccharide (LPS), a cell-associated glycolipid that makes up the outer leaflet of the outer membrane of Gram-negative bacteria, is a canonical mediator of microbe-host interactions. The most prevalent Gram-negative gut bacterial taxon, Bacteroides, makes up around 50% of the cells in a typical Western gut; these cells harbor ~300 mg of LPS, making it one of the highest-abundance molecules in the intestine. As a starting point for understanding the biological function of Bacteroides LPS, we have identified genes in Bacteroides thetaiotaomicron VPI 5482 involved in the biosynthesis of its lipid A core and glycan, generated mutants that elaborate altered forms of LPS, and used matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry to interrogate the molecular features of these variants. We demonstrate, inter alia, that the glycan does not appear to have a repeating unit, and so this strain produces lipooligosaccharide (LOS) rather than LPS. This result contrasts with Bacteroides vulgatus ATCC 8482, which by SDS-PAGE analysis appears to produce LPS with a repeating unit. Additionally, our identification of the B. thetaiotaomicron LOS oligosaccharide gene cluster allowed us to identify similar clusters in other Bacteroides species. Our work lays the foundation for developing a structure-function relationship for Bacteroides LPS/LOS in the context of host colonization.